Data from proteomic analysis of the skin of Chinese giant salamander (Andrias davidianus) - Geng, Xiaofang (Data Brief, 2015)
The Chinese giant salamander (Andrias davidianus), renowned as a living fossil, is the largest and longest-lived amphibian species in the world. Its skin is rich in collagens, and has developed mucous gland which could secrete a large amount of mucus under the scraping and electric stimulation. The molting is the degraded skin stratum corneum. To establish the functional skin proteome of Chinese giant salamander, two-dimensional gel electrophoresis (2DE) and mass spectrometry (MS) were applied to detect the composition and relative abundance of the proteins in the skin, mucus and molting. The determination of the general proteome in the skin can potentially serve as a foundation for future studies characterizing the skin proteomes from diseased salamander to provide molecular and mechanistic insights into various disease states and potential therapeutic interventions. Data presented here are also related to the research article “Proteomic analysis of the skin of Chinese giant salamander (Andrias davidianus)” in the Journal of Proteomics [1].